Association of healthcare fragmentation with three-year survival among kidney transplant recipients in Colombia. - Luis Manuel Barrera-Lozano; Daniela Sánchez-Santiesteban; Giancarlo Buitrago (PLoS ONE)
Objective Kidney transplantation requires a multidisciplinary approach to achieve optimal outcomes. Healthcare fragmentation, defined by inadequate communication and lack of integration among providers, disrupts the continuum of care, leading to adverse clinical outcomes. Latin American countries face significant challenges in delivering integrated healthcare. This fragmentation is further exacerbated in Colombia by the decentralized structure of the healthcare system, which disperses responsibilities across multiple actors, including public and private providers, insurers, and regional authorities. This study aimed to assess healthcare fragmentation in kidney transplant patients during their first post-transplant year and evaluate its association with three-year survival among patients enrolled in Colombia's contributory healthcare scheme. Methods A retrospective cohort study was conducted using administrative data from Colombia's contributory healthcare scheme. The cohort included kidney transplant recipients (2012-2016) who survived the first post-transplant year. Healthcare fragmentation was measured by the number of unique providers involved in the first year. Patients were categorised into high- and low-fragmentation groups based on the 75th percentile of provider distribution. The primary outcome was three-year survival, analysed using multivariate Cox regression to estimate hazard ratios (HRs), adjusted for age, sex, Charlson Comorbidity Index (CCI), insurer, region, and transplant year. Results The cohort comprised 2,028 kidney transplant patients, with a mean age of 47.7 years (SD: 13.4), 38.7% female, and 68.7% presenting a CCI ≤ 3. Healthcare fragmentation ranged from 1 to 34 providers, with a mean of 8.94 (SD: 6.77). High fragmentation (≥11 providers) was observed in 30.2% of patients. Three-year mortality was significantly higher in the high-fragmentation group (18%) compared to the low-fragmentation group (12%) (p = 0.04). High fragmentation was associated with a 49% increased mortality risk (adjusted HR: 1.49; 95% CI: 1.12-1.97; p = 0.01). Conclusion These findings underscore the importance of integrated care models and improved coordination among providers to enhance patient outcomes, particularly in resource-limited settings.